Visualization of Atom Transfer Radical Polymerization by Aggregation‐Induced Emission Technology. Issue 7 (4th March 2020) - Wang, Xin; Qiao, Xiaoguang; Yin, Xiuzhe; Cui, Zhe; Fu, Peng; Liu, Minying; Wang, Guowei; Pan, Xiangcheng; Pang, Xinchang
Abstract: Aggregation‐induced emission (AIE) technology has been demonstrated to be a facile approach for in‐situ monitoring atom transfer radical polymerization (ATRP). A series of tertraphenyl ethylene (TPE)‐containing α‐bromo compounds were synthesized and applied as ATRP initiators. The photoluminescent (PL) emission of the polymerization system is proved to be sensitive to the local viscosity owing to the AIE characteristics of TPE. Linear relationships between the resulting molecular weight M n and PL intensity were observed in several polymerization systems with different monomers, indicating the variability of this technique. Compared to physical blending, the chemical bonding of the TPE group in the chain end has higher sensitivity and accuracy to the polymer segments and the surrounding environment. This work promoted the combination of the AIE technique and controlled living radical polymerization, and introduced such an optical research platform to the ATRP polymerization process. Abstract : Visualization of atom transfer radical polymerization was achieved at the molecular level with non‐invasive detection assisted by tetraphenylethylene‐functionalized initiator with aggregation‐induced emission behavior.